Photodynamic therapy and Photobiomodulation as adjuvant treatment of oral and facial manifestations in patients with COVID-19 hospitalized in the intensive care unit: a case series (Research, Society and Development, 2022)
Orofacial injuries resulting from Coronavirus-19 (COVID-19) are reported in the current literature. The etiology of these manifestations is still unknown, but them seem to have an association between the prone position and patient’s immunosuppression. Clinical features range from nonspecific ulcers to vesicles that may mimic viral infections. The search for a clinical protocol for the cure of these lesions is necessary. Thus, some studies about photobiomodulation, a low-level light therapy with regenerative tissue action, associated with antimicrobial photodynamic therapy, as a promising adjuvant treatment. Therefore, the present study aims to report a series of cases where photobiomodulation and photodynamic therapy were used in patients positive for COVID-19 and presented orofacial lesions during the time of hospitalization in the intensive care unit. In all cases, tissue regeneration was complete, demonstrating the effectiveness of photobiomodulation and photodynamic therapy as adjuvant therapy associated with the use of medicines.